A Survey Paper on Inter-carrier Interference Reduction Techniques in OFDM Systems - Ahirwar, Brijesh; Pasi, Vishal (International Journal of Computer Sciences and Engineering, 2025)
Orthogonal Frequency Division Multiplexing (OFDM) is a multicarrier modulation technique that divides the available spectrum into many carriers. The efficient use of the spectrum makes it more suitable for transmitting high speed data candidate. However, the main drawback is its sensitivity to CFO causing Inter Carrier Interference (ICI). The Orthogonal Frequency Division Multiplexing systems (OFDM) suffering from interference between carriers in mobile environment due to loss of orthogonality between subcarriers caused by Doppler shifts. Many ICI Reduction techniques in this paper, to improve the performance of OFDM systems. This ICI causes severe degradation of the bit error rate (BER) of OFDM receiver. There are numerous techniques for reducing ICI windows, including time domain, frequency domain equalization, matrix technique and ICI self-cancellation.